EFISIENSI KINERJA KEUANGAN BADAN AMIL ZAKAT DAERAH (BAZDA): PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) - Lestari, Alfi (Jurnal Ekonomi & Studi Pembangunan, 2015)
Abstract: The great potential of Zakat, Infak and Sedekah (ZIS) in East Lombok Regency is believed to be able to create justice wealth distribution and welfare of the people. However, received ZIS funds have not yet been optimal and is still far from the potential of Zakat. So that, it was needed of optimizing the potential of Zakat, one only measured from high efficiency. This research aims to analyze efficiency financial performance of Regional Zakat Institution (BAZDA) by using Data Envelopment Analysis (DEA) method with intermediations approach. Quantitative approach is conducted in this descriptive research. The object in this research is financial report BAZDA East Lombok Regency in period 2012-2014. This research applied Data Envelopment Analysis method with Constant Return to Scale (CRS) asumption. There are two variables that have been used in this research is the input and output variables. The input variables are received ZIS funds, operating cost and wage staff. While the output variables are allocated ZIS funds and fixed assets. The Results of these studies indicate that BAZDA in East Lombok Regency, efficiency at the end of 2012-2014 was 100 percent. Efficiency goes on because the actual is t same as a target that was determined by DEA.Â Abstrak: Besarnya potensi Zakat, Infak dan Sedekah (ZIS) di Kabupaten Lombok Timur diyakini dapat menciptakan keadilan distribusi kekayaan dan kesejahteraan masyarakat. Akan tetapi, dana ZIS yang terhimpun belum optimal dan masih jauh dari potensi zakat yang ada. Sehingga dibutuhkan optimalisasi potensi zakat, salah satunya diukur dari tingkat efisiensinya. Studi ini bertujuan untuk menganalisis Efisiensi Kinerja Keuangan Badan Amil Zakat Daerah (BAZDA) menggunkan metode Data Envelopment Analysis (DEA) dengan pendekatan intermediasi. Objek yang diteliti adalah laporan keuangan BAZDA Kabupaten Lombok Timur periode 2012-2014. Metode yang digunakan adalah metode Data Envelopment Analysis (DEA) dengan asumsi Constant Return to Scale (CRS). Ada dua variabel yang digunakan dalam studi ini yaitu variabel input dan output. Variabel input yang digunakan adalah dana ZIS yang terhimpun, aktiva tetap dan gaji karyawan. Sementara variabel outputnya adalah dana ZIS yang tersalurkan dan biaya operasional. Hasil studi ini menunjukkan bahwa BAZDA Kabupaten Lombok Timur mengalami efisiensi pada tahun 2012-2014 yaitu sebesar 100 persen. Efisiensi terjadi karena nilai actual tidak sama dengan nilai target yang ditetapkan oleh DEA.